2017
DOI: 10.1101/194019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of genetic correlation using linkage disequilibrium score regression and genomic restricted maximum likelihood

Abstract: 20Genetic correlation is a key population parameter that describes the shared genetic architecture 21 of complex traits and diseases. It can be estimated by current state-of-art methods, i.e. linkage 22 disequilibrium score regression (LDSC) and genomic restricted maximum likelihood (GREML). 23The massively reduced computing burden of LDSC compared to GREML makes it an attractive 24 tool for analyses of many traits, achieved through use of GWAS summary statistics rather than 25 individual level genotype data. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Recently, a study suggested that rA estimates from LDSC are less accurate than rA obtained by GREML(d), perhaps because of the uncertainty of homogeneity among combined data sets. 31 Still, our twin-SEM and SNP-GREML(d) models give estimates of rA and rE largely in agreement with each other for most correlated cardiometabolic pairs.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, a study suggested that rA estimates from LDSC are less accurate than rA obtained by GREML(d), perhaps because of the uncertainty of homogeneity among combined data sets. 31 Still, our twin-SEM and SNP-GREML(d) models give estimates of rA and rE largely in agreement with each other for most correlated cardiometabolic pairs.…”
Section: Discussionsupporting
confidence: 71%
“…However, the estimates of rA from LDSC were >1 for 4 pairs of blood lipids, indicating potential inflation in signal, potentially resulting from using overlapped individuals (Table ) or imputed SNPs to capture the covariation. Recently, a study suggested that rA estimates from LDSC are less accurate than rA obtained by GREML(d), perhaps because of the uncertainty of homogeneity among combined data sets . Still, our twin‐SEM and SNP‐GREML(d) models give estimates of rA and rE largely in agreement with each other for most correlated cardiometabolic pairs.…”
Section: Discussionmentioning
confidence: 57%
“…The UKBB1+GIANT2015 estimate was reported by Ni et al 23 Bars are 95% confidence interval. For RNM, the model was y = α0+ α1×c + e. For RR-GREML and GCI-GREML, the model was y = α0+ α1×c + e. In RR-GREML and GCI-GREML, samples were arbitrarily stratified into four different groups according to the covariate levels.…”
Section: Softwarementioning
confidence: 95%
“…There is no current literature on the expected standard error or power from LD score regression, however it can be compared to those expected from the linear mixed model maximum likelihood method (GREML), which estimates SNP-heritabilities and genetic correlations from GWAS genotype data (Visscher et al, 2014). Empirical comparisons have shown that the error associated with using LD score regression is approximately fifty percent larger than that of GREML (Ni et al, 2017). Using the GCTA- Table 2A †=…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, as genotyping becomes cheaper, genomewide SNP data is becoming more readily and widely available than pedigree data. Moreover, unbiased estimates of genetic correlations are achievable with minimal computing resources from analysis of summary statistics from genome-wide association studies via the LD-score regression method (Bulik-Sullivan et al, 2015a; Ni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%